The status of intercellular junctions in established lens epithelial cell lines - Dave, Alpana (Molecular Vision, 2012)
PURPOSE: Cataract is the major cause of vision-related disability worldwide. Mutations in the crystallin genes are the most common known cause of inherited congenital cataract. Mutations in the genes associated with intercellular contacts, such as Nance-Horan Syndrome (NHS) and Ephrin type A receptor-2 (EPHA2), are other recognized causes of congenital cataract. The EPHA2 gene has been also associated with age-related cataract, suggesting that intercellular junctions are important in not only lens development, but also in maintaining lens transparency. The purpose of this study was to analyze the expression and localization of the key cell junction and cytoskeletal proteins, and of NHS and EPHA2, in established lens epithelial cell lines to determine their suitability as model epithelial systems for the functional investigation of genes involved in intercellular contacts and implicated in cataract. METHODS: The expression and subcellular localization of occludin and zona occludens protein-1 (ZO-1), which are associated with tight junctions; E-cadherin, which is associated with adherence junctions; and the cytoskeletal actin were analyzed in monolayers of a human lens epithelial cell line (SRA 01/04) and a mouse lens epithelial cell line (αTN4). In addition, the expression and subcellular localization of the NHS and EPHA2 proteins were analyzed in these cell lines. Protein or mRNA expression was respectively determined by western blotting or reverse transcription-polymerase chain reaction (RT–PCR), and localization was determined by immunofluorescence labeling. RESULTS: Human SRA 01/04 and mouse αTN4 lens epithelial cells expressed either the proteins of interest or their encoding mRNA. Occludin, ZO-1, and NHS proteins localized to the cellular periphery, whereas E-cadherin, actin, and EPHA2 localized in the cytoplasm in these cell lines. CONCLUSIONS: The human SRA 01/04 and mouse αTN4 lens epithelial cells express the key junctional proteins. The localization patterns of these proteins suggest that these cell lines form tight junctions but do not form E-cadherin-based adherence junctions. These data further indicate that the regulatory role of NHS in actin remodeling, suggested in another study, is cell type dependent. In conclusion, the SRA 01/04 and αTN4 lens epithelial cell lines model some characteristics of an epithelium.